AQA information & communication technology for A2 level - Mott, Julian; Leeming, Anne; Williams, Helen (London : Hodder Education, 2009)
This title has been thoroughly revised and updated to meet the demands of the revised AQA specification, supporting flexible delivery and greater opportunities for practical work.
Includes index.
Keywords: Information technology; Telecommunication; Computer science; Computers and IT